The Influence of Emotional Intelligence and Work Culture on Work Commitment and Its Implications on Nurse Performance - Agustin, Farida; Affandi, Azhar; Setiawan, Heru (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study examines the influence of Emotional Intelligence and Work Culture on Work Commitment and its implications for Nurse Performance in hospitals in the Banten Province. Nurses play a pivotal role in the delivery of quality healthcare services, directly impacting patient recovery and overall hospital performance. The study adopts a quantitative approach with a survey method, collecting data from nurses at four city hospitals in Banten. The results show that both Emotional Intelligence and Work Culture have a significant positive effect on Work Commitment, which in turn, strongly influences Nurse Performance. Emotional Intelligence enables nurses to manage their emotions effectively, fostering stronger emotional engagement with their work. Meanwhile, a supportive Work Culture enhances collaboration and communication among nurses, further strengthening their commitment to their jobs. The findings also reveal that Work Commitment serves as a crucial mediator in the relationship between Emotional Intelligence, Work Culture, and Nurse Performance. Nurses with higher Emotional Intelligence are better equipped to handle stress and build stronger relationships with patients and colleagues, leading to improved performance. Similarly, a positive Work Culture fosters an environment where nurses feel valued and supported, increasing their dedication and job satisfaction. The study concludes that hospitals should prioritize strategies to enhance Emotional Intelligence and cultivate a positive Work Culture to improve both nurse performance and the overall quality of healthcare services.